Pengembangan Aplikasi E-Commerce Menggunakan Payment Gateway Midtrans - Fariz Reynaldo Pratama; Nurudin Santoso; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Anfield collection is a handicraft factory and a shop that sells handicrafts. When running its business anfield store will record stock and display products in its own shop and in partner stores. There are 25 types of products on sale at anfield stores, it is difficult to remember the different product variations and prices. Then, when a transaction is made anfield officer will provide a receipt to the buyer and then record it in the transaction register book. The marketing that has been done is not too broad, this is felt by the shop owner, the reason being that it is not good enough in utilizing information technology. The number of similar businesses also makes Anfield have to compete with other stores. Anfield business owners mention that it needs special e-commerce applications for anfield producers to overcome problems and improve the quality of business processes that run in terms of effectiveness and efficiency. Therefore, e-commerce applications are made on the mobile platform. In the application there are basic features in buying and selling online, namely managing products, ordering, payment transactions and expeditions. The distinguishing feature is the category of craft products based on the type, process and main ingredients. To handle payment transactions applications must be able to handle various types of payments. This application has been tested using the white-box method with unit testing and Usability Testing with the standard Post Study System Usability Questionnaire (PSSUQ). Test result show that requirement has passed 100% and generally average user is satisfied while using the application.